Pengaruh Penggunaan Media Pembelajaran terhadap Hasil Belajar Siswa - Khadijah Gani Harahap; Hikmah Pradana (Departement of Mathematics Education, 2024)
The use of appropriate learning media in accordance with the characteristics needed can encourage the improvement of student learning outcomes, this is due to the importance of using media in learning. The purpose of this study was to describe the effect of using learning media on student learning outcomes. The method used in this research is the library study method or literature with library data collection methods, reading and recording and processing research materials. The results of this study indicate that learning media is very influential in the world of education, because the use of learning media makes it easier for educators to apply the material they teach, as well as students to easily accept learning. The function of using learning media is to attract and direct students' attention to concentrate on the content of the lesson. That is why its use must be adjusted and related to the subject matter to be given, so that it can improve student learning outcomes.